Ion irradiation and radiation effect characterization at the JANNUS-Saclay triple beam facility. Issue 9 (11th February 2015) - Beck, Lucile; Serruys, Yves; Miro, Sandrine; Trocellier, Patrick; Bordas, Eric; Leprêtre, Frédéric; Brimbal, Daniel; Loussouarn, Thomas; Martin, Hervé; Vaubaillon, Sylvain; Pellegrino, Stéphanie; Bachiller-Perea, Diana
Abstract: Abstract : JANNUS (Joint Accelerators for Nanosciences and Nuclear Simulation), the unique triple beam facility in Europe, offers the possibility to produce three ion beams simultaneously for nuclear recoil damage and implantation of a large array of ions for well-controlled modeling-oriented experiments. The first triple beam irradiation was performed in March 2010. Along with irradiation developments, continuous efforts have been made to implement ex situ and in situ characterization tools. In this study, we set out the present status of the JANNUS facility of the Saclay site. We focus on the instrumentation used for conducting multi-ion beam irradiations and implantations as well as for characterizing bombarded samples. On-line control of irradiation parameters, in situ modification monitoring using Raman spectroscopy or ion beam induced luminescence, and ex situ characterization by ion beam surface analysis [Rutherford backscattering spectrometry (RBS), nuclear reaction analysis (NRA), and elastic recoil detection analysis (ERDA)] of implanted samples are detailed. Some examples of single, dual, and triple beam irradiation configurations are presented. Access to the facility is provided by the French network EMIR for national and international users (http://emir.in2p3.fr/ ).